Non-Hemodynamic Effects of Catecholamines. Issue 4 (October 2017) - Hartmann, Clair; Radermacher, Peter; Wepler, Martin; Nußbaum, Benedikt
Abstract : ABSTRACT: Circulatory shock is defined as an imbalance between tissue oxygen supply and demand, and mostly results from a loss of blood volume, cardiac pump failure, and/or reduction of vasomotor tone. The clinical hallmarks of circulatory shock are arterial hypotension and lactate acidosis. Since the degree and duration of hypotension are major determinants of outcome, vasopressor administration represents a cornerstone therapy to treat these patients. Current guidelines recommend the use of catecholamines as the drug of first choice. However, apart from their hemodynamic effects, which depend on the different receptor profile, receptor affinity, receptor density, and the relative potency of the individual molecule, catecholamines have numerous other biological effects as a result of the ubiquitous presence of their receptors. In shock states, catecholamines aggravate hypermetabolism by promoting hyperglycemia and hyperlactatemia, and further increase oxygen demands, which can contribute to further organ damage. In the mitochondria, catecholamines may promote mitochondrial uncoupling, and aggravate oxidative stress, thereby contributing to the progression of mitochondrial dysfunction. Immunological side effects have also gained specific attention. Although both pro- and anti-inflammatory effects have been described, current evidence strongly indicates an immunosuppressive effect, thereby making patients potentially vulnerable to secondary infections. Catecholamines may not only decrease splanchnic perfusion due to their vasoconstrictor properties, but can also directly impair gastrointestinal motility. This article reviews the non-hemodynamic effects of different catecholamines, both under physiologic and pathophysiologic conditions, with a special focus on energy metabolism, mitochondrial function, immune response, and the gastrointestinal system.